The Influence of Brand Experience, Brand Loyalty, and Brand Love on the Willingness to Pay a Premium Price among Samsung Smartphone Customers in Malang Raya - Sari, Titis Ragilia Luxyta; Handayanto, Eko; Sa'diyah, Chalimatuz (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
This study aims to analyze brand experience, brand loyalty, and brand love to the willingness to pay a Premium price. The sampling technique used was purposive sampling with a total sample of 114 samples of Samsung smartphones in Malang. The type of data used in this study was quantitative data and the data sources were primary data. The analysis tool used in this study is multiple regression analysis. The results of this study concluded that Brand Experience, Brand Loyalty, and Brand Love have a positive and significant effect on the willingness to pay Premium prices. Thus increasing Brand Experience, Brand Loyalty, and Brand Love for consumers Samsung Electronics Co. Samsung Electronics Co., Ltd. on Samsung Smartphone products to better understand what is an important component in product development.